INFLUENCING FACTORS OF BLOOD DONATION INTENT: PROPOSING AN EXPLORATORY MODEL - Jefferson Rodrigues Pereira (Revista de Administração da Universidade Federal de Santa Maria, 2020)
Purpose: Identify the main factors that significantly influence individuals living in the metropolitan region of Belo Horizonte / MG to donate blood.Design/methodology/approach: Methodologically, it was decided to develop a quantitative research, developed in the light of structural equation modeling, allowing the development of an exploratory behavioral model about the intention to donate blood.Findings: As main results, it was identified that the ‘attitude towards screening’ contributes significantly to the ‘perception of safety’ that the individual has about the process of blood donation.Research limitations/implications: Difficulty of access to the main hemotherapy center in the state, Minas Gerais Blood Bank Foundation (HEMOMINAS), a fact that prevented access to up-to-date data on the region’s blood donation scenario.Practical implications: The indicators that are directly related to the practice of blood donation obtained statistically significant mean differences between the group of individuals who already donated blood and those who never donated, the former being more sensitive to calls for donation.Originality/value: There is a deepening of the knowledge of the variables that influence the individual who voluntarily performs an act such as blood donation. In this sense, this study provides inputs for the development of more assertive, efficient and effective blood donation public policies, contributing to the recovery of blood banks and raising the rate of donors in the country.